2020
DOI: 10.1021/acs.nanolett.0c02986
|View full text |Cite
|
Sign up to set email alerts
|

A 3D Printable Electroconductive Biocomposite Bioink Based on Silk Fibroin-Conjugated Graphene Oxide

Abstract: Reduced graphene oxide (rGO) has wide application as a nanofiller in the fabrication of electroconductive biocomposites due to its exceptional properties. However, the hydrophobicity and chemical stability of rGO limit its ability to be incorporated into precursor polymers for physical mixing during biocomposite fabrication. Moreover, until now, no suitable rGOcombining biomaterials that are stable, soluble, biocompatible, and 3D printable have been developed. In this study, we fabricated digital light process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 48 publications
0
42
1
Order By: Relevance
“…It has been previously reported that GO may demonstrate certain cytotoxicity due to hydrophobic interaction with cell membranes and subsequent extraction of membrane cholesterol and phospholipids. 45 However, this phenomenon has not been observed in our experiments. One possible explanation is that the hydrophobic GO was successfully incorporated into polymeric networks, thereby enhancing its biocompatibility.…”
Section: Resultscontrasting
confidence: 73%
“…It has been previously reported that GO may demonstrate certain cytotoxicity due to hydrophobic interaction with cell membranes and subsequent extraction of membrane cholesterol and phospholipids. 45 However, this phenomenon has not been observed in our experiments. One possible explanation is that the hydrophobic GO was successfully incorporated into polymeric networks, thereby enhancing its biocompatibility.…”
Section: Resultscontrasting
confidence: 73%
“…However, the roughness induced by the carbonaceous flakes favored the protein absorption capacity and, at the same time, improved cell adhesion and proliferation in comparison with neat protein-based scaffolds. Ajiteru et al [146] were the first to develop a 3D printable bioink formulation based on an SF-conjugated rGO structure that, after photocuring, exhibited similar mechanical and electrical properties to those of the spinal tissue. The ability of the bionanocomposite to support the viability and proliferation of Neuro2a cells makes it a suitable candidate for the development of neural tissue engineering platforms.…”
Section: Nerve Tissuementioning
confidence: 99%
“…[ 203 ] Recently, Ajiteru et al. [ 204 ] developed a printable bioresin for neural tissue engineering, through covalent reduction of graphene oxide (GO) by glycidyl methacrylated silk fibroin. The resin was capable of printing complex shapes as shown in Figure 10a.…”
Section: Bioresins and Recent Advancesmentioning
confidence: 99%
“…Reproduced with permission. [ 204 ] Copyright 2020, ACS Publications, b) i–iv) Cell distribution inside the Sil‐MA hydrogels. The Sil‐MA hydrogels with i) a design of the letter HL (the logo of Hallym University), ii) a shape of human brain were printed out with PKH67‐labeled cells only, iii) the Sil‐MA hydrogels with the letter HL, and iv) a shape of winding trachea were printed out with PKH67‐labeled cells (green) and PKH26‐labeled cells (red); (from left to right) CAD images, printed images, fluorescence images by (i) confocal or (ii–iv) single plane illumination microscopy (SPIM) microscope, and merged images of fluorescence and CAD images.…”
Section: Bioresins and Recent Advancesmentioning
confidence: 99%